2019
DOI: 10.1007/s11105-019-01164-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Pattern Analysis of Bacterial Blight Resistance Genes in Oryza officinalis Wall ex Watt Under Xanthomonas oryzae Pv. oryzae Stress

Abstract: Background Bacterial blight (BB) caused by Xanthomonas oryzae Pv. oryzae (Xoo) is one of the most serious diseases of rice worldwide. Oryza officinalis Wall ex Watt, harboring abundant genetic diversity and disease resistance features, are important resources of exploring resistance genes with broad-spectrum resistance to BB. However, the molecular mechanisms and genes of BB resistance in O. officinalis have been rarely explored. Results Here, the BB resistance of four different origin O. officinalis populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Some previous studies have reported phenotypic resistance to BB in rice by the leaf-clipping method (Fred et al 2016;Jiang et al 2019). Molecular markers can greatly facilitate the development of new disease resistant materials, and effectively detect the presence of BB resistance genes in rice (Ullah et al 2012;Hur et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous studies have reported phenotypic resistance to BB in rice by the leaf-clipping method (Fred et al 2016;Jiang et al 2019). Molecular markers can greatly facilitate the development of new disease resistant materials, and effectively detect the presence of BB resistance genes in rice (Ullah et al 2012;Hur et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…All strains were cultured on Nutrient Agar medium by 28℃ for 48 h, then resuspended in double distilled water, and diluted to OD 600 nm = 0.8 for inoculation by using the NanoDrop2000. Each rice accession at booting stage (panicle development) was respectively inoculated with Xoo strains by the leafclipping method at 15:00 ~ 17:00 (Jiang et al 2019). Three replicates (three individual plants) for each accession were designed for each Xoo strain with five leaves inoculated per plant.…”
Section: Xoo Strains Inoculation and Phenotypic Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The inducible expression of Rph3. Most cloned disease resistance genes are expressed constitutively 60,61 . Constitutive expression was observed in genes conferring resistance to various pathogens, including bacteria [62][63][64] and fungi [65][66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have isolated and characterized several genes for disease resistance from O. officinalis Wall. ex Watt (Jiang et al 2019 ), however, the identities of genes for grain size and plant architecture are unknown.…”
Section: Introductionmentioning
confidence: 99%